The Effect of Clamping Force on the Wear Behavior of a Steam Generator Tube - Xuxin Dong; Kunlun Xu; Mingjue Zhou; Yuebing Li; Weiya Jin; Zengliang Gao; Lichen Tang (Applied Sciences, 2022)
Anti-vibration bars (AVBs) are essential components of a steam generator (SG) and are used to prevent steam generator tubes (SGTs) from vibrating intensely because of flow-induced vibration. However, the contact force generated at contact surfaces between AVBs and tubes can change the natural frequency and wear behavior of the tube. Contact force is represented by clamping force in this study. Considering the effect of the clamping force on the natural frequency and sliding distance of SGT, dynamic wear behavior under different clamping forces was analyzed based on the finite element method, and the natural frequency of the tube was measured in the present work. Moreover, the wear experiment was conducted at room temperature to verify the conclusions of dynamic behavior analysis. The increase in clamping force reduces the sliding distance of SGT, and wear depth affected by both clamping force and sliding distance also decreases.